Comparing the impacts of aerosolization and sampling techniques on the structural integrity and antigenicity retention of influenza A virus-like particles - Li, Yuezhi (August); Benegal, Ananya; Puthussery, Joseph V.; You, Shu-Wen; Vahey, Michael D.; Chakrabarty, Rajan K. (Journal of aerosol science, 2026)
Laboratory experiments studying respiratory virus aerosols rely on the reproducibility of aerosolization and sampling techniques. Conventional techniques could compromise viral structure and antigenicity, particularly for pleomorphic viruses like influenza A (IAV), yet very little information is available on this issue. Here, we evaluate three aerosolization methods: Collison, Blaustein Atomization Modules (BLAM), and jet nebulizers, and three bioaerosol samplers: liquid spot sampler (LSS), wet cyclone, and SKC BioSampler, to determine their efficiency in retaining the structural stability and antigenicity of filamentous IAV virus-like particles (VLPs). VLPs provide a safe and practical alternative for studying highly pathogenic airborne viruses. The BLAM and jet nebulizers maintain 12–21 % of filamentous structures, whereas the Collison nebulizer, which generates higher shear stress, reduces filament recovery to ∼10 %. The liquid spot sampler (LSS), owing to gentle condensation-based sampling technique, retains approximately 30 % of filamentous VLPs. The SKC BioSampler and wet cyclone sampler cause greater structural disruption due to higher shear stress and impaction forces and retain ∼10 % and ∼7 % of filamentous VLPs, respectively. Higher relative humidity (85 %) improves filament retention by ∼20 % compared to dry conditions (25 % RH). The antigenicity of Neuraminidase (NA), the IAV surface protein responsible for viral release, followed a bimodal distribution, with up to 20 % of small VLPs showing undetectable NA signal post-aerosolization, indicating greater susceptibility to structural degradation. These results point to the necessity of improving upon contemporary aerosolization and sampling strategies to characterize airborne filamentous viruses in controlled laboratory environments more accurately. •Virus-like particles (VLPs) as a proxy for live viruses in lab experiments.•Compared nebulizers and samplers for influenza VLP morphology and antigenicity.•Liquid spot sampler showed highest retention of filamentous virion morphology.•All three nebulizers showed 10–20 % retention in virion morphology.•The neuraminidase antigenicity of aerosolized VLPs showed a binary loss pattern.